Characterization of recombinant phytochrome from the cyanobacterium Synechocystis - Lamparter, Tilman (The National Academy of Sciences of the USA, 1997)
The complete sequence of the Synechocystis chromosome has revealed a phytochrome-like sequence that yielded an authentic phytochrome when overexpressed in Escherichia coli. In this paper we describe this recombinant Synechocystis phytochrome in more detail. Islands of strong similarity to plant phytochromes were found throughout the cyanobacterial sequence whereas C-terminal homologies identify it as a likely sensory histidine kinase, a family to which plant phytochromes are related. An ≈300 residue portion that is important for plant phytochrome function is missing from the Synechocystis sequence, immediately in front of the putative kinase region. The recombinant apoprotein is soluble and can easily be purified to homogeneity by affinity chromatography. Phycocyanobilin and similar tetrapyrroles are covalently attached within seconds, an autocatalytic process followed by slow conformational changes culminating in red-absorbing phytochrome formation. Spectral absorbance characteristics are remarkably similar to those of plant phytochromes, although the conformation of the chromophore is likely to be more helical in the Synechocystis phytochrome. According to size-exclusion chromatography the native recombinant apoproteins and holoproteins elute predominantly as 115- and 170-kDa species, respectively. Both tend to form dimers in vitro and aggregate under low salt conditions. Nevertheless, the purity and solubility of the recombinant gene product make it a most attractive model for molecular studies of phytochrome, including x-ray crystallography.